Elevation‐dependent changes in the trend of reference evapotranspiration in the Tibetan Plateau during 1960–2017. (27th December 2022) - Chang, Yaping; Ding, Yongjian; Zhao, Qiudong; Qin, Jia; Zhang, Shiqiang
Abstract: Elevation plays a crucial role in modulating the spatiotemporal distributions of climatic variables in mountainous regions, which affects water and energy balances, among which reference evapotranspiration (ET0 ) is a key hydrological indicator. However, the response of ET0 to climate change with elevation continues to be poorly understood, especially in the Tibetan Plateau (TP) which has elevation variations of more than 4, 000 m. The spatiotemporal variations of ET0 with elevation were investigated using long‐term (1960–2017) meteorological observations from 82 stations on the TP. The results suggest that the average annual ET0 showed an insignificant increasing trend. A significant negative correlation between ET0 and elevation was found ( p  < .01). The positive trends of ET0 decreased with elevation, whereas the negative trends of ET0 increased significantly with elevation ( p  < .05). The magnitude of trends of ET0 becomes smaller at higher‐elevation stations. Sensitivity analysis indicated that ET0 was most sensitive to shortwave radiation ( R s ). Moreover, the sensitivities of temperature ( T ) and wind speed ( U ) significantly decreased with elevation, whereas those of R s and vapour pressure deficit (VPD) increased slightly with elevation. The contribution and path analyse indicated that increasing VPD was the dominant contributor to the increase in ET0 . The effect of elevation on ET0 variation mainly depended on the tradeoff between the contributions of U and VPD. U was the largest contributing factor for the change in ET0 below 2, 500 m, whereas VPD was the primary contributor to the increase in ET0 above 2, 500 m. This study provides insights into the response of ET0 to climate change with elevation on the TP, which is of great significance to hydrometeorological processes in high‐altitude regions. Abstract : Annual and seasonal ET0 decreased significantly with elevation in the TP. The trends of annual ET0 were strongly correlated with elevation. VPD was the dominant contributor for the variation of ET0 at high elevations, while U dominated the variation of ET0 at low elevations.